Unusual site of disseminated Staphylococcus infection: erosive chest wall abscess - Gew, Lai Teck; Ng, Fei Yin; Hoo, Fan Kee (Pakistan Medical Association Rawalpindi Islamabad Branch, 2014)
Erosive chest wall abscess as a complication following disseminated Staphylococcus aureus infection is rare. Here, we reported a case of disseminated Staphylococcus aureus infection with an erosive chest wall abscess. A 15 year-old gentleman, presented with 2 days of left knee swelling and high grade fever for 1 week’s duration. On admission, he was in sepsis with multiorgan dysfunction. Further investigations revealed that he had left calf abscess, tricuspid valve infective endocarditis, bilateral pulmonary septic emboli with loculated pleural effusion, bilateral pyelonephritis with left renal abscess, and chest wall abscess. The striking feature was the presence of the abscess which extended through the sternum into the mediastinum with manubriosternal dislocation, involvement of bilateral sternoclavicular joints and left clavicle cortical erosion. Both cultures from blood and pus (left calf abscess) grew Methicillin Sensitive Staphyloccus Aureus (MSSA).